Incisões relaxadoras e resistência à tração na parede abdominal de suínos - Pedroso, Aline Ribeiro (2019)
Introduction: Some complications, such as wound dehiscence and incisional hernia (IH), may arise after surgical closure of the abdominal cavity, with excessive tension in the suture line being a major cause. In order to correct IH, Alcino Lázaro da Silva developed the bilateral longitudinal peritoneo-aponeurotic transposition technique (TRANSPALB), which uses the hernial sac to close the defect after performing relaxing incisions in the rectus abdominis muscle sheath. Purpose: To analyze the resistance to medial traction of abdominal wall muscles, before and after performing relaxing incisions. Methods: Seventeen live pigs were used. After a median laparotomy, the abdominal rectus muscles (MR) were made to fit the dynamometer. Step 1 (control phase): tensile strength measured without performing relaxant incisions. Step 2: A curvilinear relaxant incision was made on the anterior slide of the right MR sheath and then the resistance edge was measured by the edge of the wound. The same procedure was adopted after incision of the left posterior lamina. Step 3: Relaxing incisions were made on the right and left anterior slides, so that both sides were left with a relaxing incision on both slides. Measurements of resistance were performed. Results: There was no significant difference between the sides. On the right and left side, all treatments reduced the tensile strength when compared to each other and to the control. There was a reduction of 12% and 9.8% after incision of the anterior and posterior lamina, respectively. Conclusion: Relaxing incisions reduced tensile strength on the ventral abdominal wall.